Are investigations anxiolytic or anxiogenic? A randomised controlled trial of neuroimaging to provide reassurance in chronic daily headache. Issue 11 (14th October 2005) - Howard, L; Wessely, S; Leese, M; Page, L; McCrone, P; Husain, K; Tong, J; Dowson, A
Abstract : Objectives: Aims were to investigate (a) whether neuroimaging in patients with chronic daily headache reassures patients or fails to reassure them and/or worsens outcome, impacting on service use, costs, health anxieties, and symptoms, and (b) whether this reassurance process occurs differentially in patients with different levels of psychological morbidity. Methods: Design: randomised controlled trial; setting: headache clinic in secondary care, South London; participants: 150 patients fulfilling criteria for chronic daily headache, stratified using the Hospital Anxiety and Depression Scale (HADS); intervention: treatment as usual or the offer of an MRI brain scan; main outcome measures: use of services, costs, and health anxiety. Results: Seventy six patients were randomised to the offer of a brain scan and 74 patients to treatment as usual. One hundred and thirty seven (91%) primary care case notes were examined at 1 year, 103 (69%) patients completed questionnaires at 3 months and 96 (64%) at 1 year. Sixty six (44%) patients were HADS positive (scored >11 on either subscale). Patients offered a scan were less worried about a serious cause of the headaches at 3 months (p = 0.004), but this was not maintained at 1 year; other health anxiety measures did not differ by scan status. However, at 1 year HADS positive patients offered a scan cost significantly less, by £465 (95% confidence interval (CI): −£1028 to −£104), than such patients not offered a scan, due to lower utilisation of medical resources. Conclusions: Neuroimaging significantly reduces costs for patients with high levels of psychiatric morbidity, possibly by changing subsequent referral patterns of the general practitioner.